Notes on the Birds of Central Oaxaca, Part II: Columbidae to Vireonidae - John M. Forcey (Huitzil. Revista Mexicana de Ornitología, 2002)
New data are presented amplifying or clarifying the status and distribution of 70 species of birds found in central Oaxacaprimarily in portions of the Districts of Centro, Etla, Ixtlan, Tlacolula, and Zaachila within 35 km of Oaxaca City.Summaries are based on observations made on 738 days during the period from Dec 1996 to Mar 2002. Principal habitatsfound in the area are pine-oak (including limited areas of pine-oak-fir and limited extensions of bunch grass mixed withpine-oak), oak scrub, arid subtropical scrub, riparian areas, and areas more or less modified for agricultural or other humanuse (including gardens and parks). The following species are newly reported from the area as vagrants or rare transientmigrants: Plain-capped Starthroat (Heliomaster constantii), Sparkling-tailed Hummingbird (Tilmatura dupontii), YellowbelliedFlycatcher (Empidonax flaviventris), Acadian Flycatcher (Empidonax virescens), Great Crested Flycatcher(Myiarchus crinitus), Sulphur-bellied Flycatcher (Myiodynastes luteiventris), Philadelphia Vireo (Vireo philadelphicus),Red-eyed Vireo (Vireo olivaceus), and Yellow-green Vireo (Vireo flavoviridis). Also, the following ten species havepreviously been reported either only on Christmas Bird Counts or as single records: Buff-collared Nightjar (Caprimulgusridgwayi) (presumed resident), Great Swallow-tailed Swift (Panyptila sanctihieronymi) (local resident), Azure-crownedHummingbird (Amazilia cyanocephala) (local resident), Green-fronted Hummingbird (Amazilia viridifrons), GarnetthroatedHummingbird (Lamprolaima rhami), Russet-crowned Motmot (Momotus mexicanus) (presumed resident SierraJuárez), Eastern Phoebe (Sayornis phoebe), Social Flycatcher (Myiozetetes similis) (resident), Gray-collared Becard(Pachyramphus major) (resident), and White-eyed Vireo (Vireo griseus). Breeding data are reported for 25 species, 18without previous breeding records here. Twenty-four of these species can be grouped together as breeding Apr to Jul.Seventeen breed in riparian areas, six of these almost exclusively so.